Effect of herbal feed additives on intake, rumen fermentation, availability of nutrients and energetic efficiency of feeds in Barbari kids reared under confined condition - CHATURVEDI, INDU; DUTTA, T K; SINGH, P K; CHATTERJEE, A; MANDAL, D K; DAS, ARUN K (The Indian Journal of Animal Sciences, 2021)
Weaned male Barbari kids (24) were divided equally into three groups (T1, T2 and T3) to investigate the effect of supplementation of herbal feed additives in the complete pelleted feed on intake of nutrients, rumen fermentation, availability of nutrients and energetic efficiency under stall-fed condition during an eight months feeding trial. Treatments were T1, Concentrate mixture (40%) plus arhar (Cajanus cajan) straw (60%) in Total Mixed Ration (TMR) form fed ad lib.; T2, Concentrate mixture (40%) plus arhar straw (60%) in Complete Feed Pellets form fed ad lib.; T3, Concentrate mixture (40%) plus arhar straw (60%) in Complete Feed Pellets form supplemented with herbal mixture (four herbs; Tulsi: Haldi: Amla: Arni, ratio 1:1:1:1 on DM basis) @ 0.5% in complete feed fed ad lib. Rumen fermentation pattern was studied at 3rd and 25th weeks of experimental feeding. A metabolism trial was conducted at the last phase of the experiment. During metabolism trial, DMI (g)/kg W0.75 and CPI (g)/kg W0.75 was greater in kids under T3 and T2 than T1. Pelleted complete feed supplemented with phytogenic feed additives resulted greater total VFA (mmol/dl SRL) concentration in rumen liquor of kids under T3 than TMR fed kids (T1) at three weeks of experimental feeding. The concentration of NH3-N (mg/dl SRL) was depressed significantly in T3 at 3rd and 25th weeks of feeding; T1 showed highest values during both periods. TDN intake (g)/kg W0.75 and Digestible Energy intake (MJ)/kg W0.75 were increased significantly in T3 and T2 than T1. DCP intake (g)/kg W0.75 was also higher in T2 and T3 than T1. Similarly, N-balance (g)/kg W0.75 increased significantly in T3 and T2 than T1. Therefore, it may be concluded that densification of feeds in the form of complete pelleted feed (T2) and further supplementation (@ 0.5% in the complete feed) with herbal mixture (Amla, Haldi, Arni and Tulsi=1:1:1:1 on DM basis) (T3) increased the intakes of DM, TDN, digestible energy and protein; enhanced rumen fermentation pattern, and increased N-balance in finisher Barbari kids.